Dielectric-loading approach for extra electric field enhancement and spatially transferring plasmonic hot-spots. (22nd October 2020) - Wan, Mingjie; Wu, Jingyu; Liu, Jun; Chen, Zhuo; Gu, Ping; Zhan, Peng; Wang, Zhenlin; Bozhevolnyi, Sergey I
Abstract: Plasmonic nanoantennas have been widely explored for boosting up light-matter interactions due to their ability of providing strongly confined and highly enhanced electric near fields, so called 'hot-spots'. Here, we propose a dielectric-loading approach for hot-spots engineering by coating the conventional plasmonic nanoantennas with a conformal high refractive index dielectric film and forming dielectric-loaded plasmonic nanoantennas. Compared to the conventional plasmonic nanoantennas, the corresponding dielectric-loaded ones that resonate at the same frequency are able to provide an extra enhancement in the local electric fields and meanwhile spatially transfer the hot spots to the dielectric surfaces. These findings have important implications for the design of optical nanoantennas with general applications in surface enhanced linear and nonlinear spectroscopies. As a demonstration application, we show that the maximum achievable fluorescence intensity in the dielectric-loaded plasmonic nanoantennas could be significantly larger than that in the conventional plasmonic nanoantennas.